Comparison of two exercise testing protocols in patients with chronic fatigue syndrome - Nijs, Jo; Zwinnen, Kim; Meeusen, Romain; de Geus, Bas; De Meirleir, Kenny (Journal of rehabilitation research and development, 2007)
This study examined whether a linear exercise stress-testing protocol generated different peak exercise performance variables than a stepwise exercise testing protocol in patients with chronic fatigue syndrome (CFS). We conducted a comparative study with patients randomly allocated to one of two exercise testing protocols. Twenty-eight women with CFS completed two self-reported measures (the CFS Symptom List and the CFS Activities and Participation Questionnaire) and then performed until exhaustion either the linear or the stepwise exercise testing protocol with continuous monitoring of physiological variables (heart rate and oxygen uptake). At baseline, we found no significant differences in demographic features and health status between groups (p > 0.05). Based on ratio peak workload/peak oxygen uptake, mechanical efficiency was lower among the subjects performing the stepwise protocol (p = 0.002). When we analyzed the mean linear regression slope values between oxygen uptake and workload from each subject's minute-by-minute exercise data points, we found that mechanical efficiency was lower among the subjects performing the stepwise protocol (p = 0.039). Apart from mechanical efficiency, we found no differences in exercise performance data between groups (p > 0.05). Our results suggest that the difference between linear and stepwise exercise protocols cannot account for all discrepancies of previous studies on exercise performance data in women with CFS, but they do suggest that the nature of the exercise testing protocol influences mechanical efficiency in these patients. Further study is warranted.